Role of DPP-4 inhibitors in the management of type 2 diabetes - ., Ramesh; Gupta, D. D. (International Journal of Basic & Clinical Pharmacology, 2018)
Among various insulinotropic agents used in treatment of Type 2 DM, inclusion of DPP4 inhibitors are considered as major breakthrough as far as new drug development is concerned. In this review article we have discussed in detail about the pathogenesis of diabetes mellitus especially the role of incretin, DPP4 enzyme and implication of its inhibitors in treatment of DM. Also, various clinical studies regarding use of DPP4 inhibitors as monotherapy and as combination therapy with other antidiabetic agents were discussed. DPP-4 inhibitors control glucose in fasting as well as in postprandial state both in monotherapy and in combination with other oral antidiabetic agents. Significant reduction in HbA1c observed with DPP4 inhibitors as monotherapy. On combining DPP 4 inhibitor as add-on therapy to metformin, glitazone or sulphonylurea therapy in patients with type 2 diabetes not reaching therapeutic goals, DPP-4 inhibitors reduce HbA1c, fasting plasma glucose and 2-h postprandial plasma glucose up to the desired level. Various DPP-4 inhibitors have been proven to be as safe and tolerable both as monotherapy and combination with other antidiabetic agents. Inhibition of DPP-4 enzyme has been proven as a promising aspect in the treatment of type 2 diabetes and various drugs inhibiting DPP4 enzymes have been developed now. They are highly recommended in the treatment of Type 2 DM both as monotherapy as well as combination therapy.